Acceleration of Debris Flow Due to Granular Effect - Yang, Taiqiang; Li, Yong; Guo, Xiaojun; Zhang, Jun; Jiang, Yu; Liu, Xuemei; Liu, Jingjing (Frontiers in Earth Science, 2021)
Pore water pressure has been recognized as an important factor to enhance the mobility of debris flow moving on channel of very gentle slope. The building and dissipation of pore water pressure are associated with interaction between grains. This study proposes a physical model for the pressure on mobility of flows with different granular structures: the reverse grading structure and the grain-mixed structure, and then the flow velocity is derived by the effective stress principle and the relationship between acceleration and pore water pressure is analyzed under different conditions. The results show that a high excess pore water pressure favors high velocity of flow, and the pressure increases during the movement; and velocity increases with time and flow depth under given pore water pressure. Moreover, comparing with the flow with grain-mixed structure, the flow with reverse grading structure has a layered concentrated load and is more effective to promote the excess pore water pressure and the liquefaction slip surface. Therefore, the internal drag reduction due to pore water pressure produces an acceleration effect on the flow.